Evaluation of the Al-Qur'an Learning Program Using the Ummi Method in Islamic Elementary Schools in Yogyakarta - Amalia, Tuti; Sudiyatno, Sudiyatno; Nurbaiti, Novita; Tuanaya, Rugaya (Universitas Islam Negeri Raden Intan Lampung, 2024)
The Ummi method for learning the Qur’an aims to teach students correct recitation from an early age. This study evaluates the implementation of Quranic learning using the Ummi method, focusing on both process and product aspects. It employs a quantitative approach as evaluation research, utilizing observation, interviews, and questionnaires for data collection. The CIPP assessment model is used to assess both process and product aspects. The study sample consisted of 25 third-grade students. The findings are as follows: (1) From the process perspective, the implementation of the Al-Qur’an study program using the Ummi method reveals issues such as students experiencing difficulties with breath control and forgetfulness. (2) From the product perspective, the study shows that the average learning achievement of third-grade students is at volume 4. Overall, the evaluation results are positive, with several recommendations from the author: (1) Students should enhance memorization skills through daily murojaah to reinforce their memorization, (2) Ummi teachers should provide tips and techniques to improve students' breath management abilities, and (3) Parents should allocate time to recite the Quran together with their children, listening to their memorization or readings daily.